Emergency management competence development: Concepts for education and exercises within emergency management in the maritime Arctic environment MARPART2-(MAN), Project Report 3 - Andreassen, Natalia; Buvarp, Paul M.H.; Kuznetsova, Svetlana; Prochotska, Jana; Suslov, Alexander; Baykina, Nadezhda (Nord universitet, 2021)
The report focuses mainly on education and training concepts for competence development for the key management personnel who can be involved in management of large scale events in the Arctic sea regions.